Whole-Plant Consequences of Crassulacean Acid Metabolism for a Tropical Forest Understory Plant - Skillman, J. B.; Garcia, M.; Winter, W.
We examined leaf and whole-plant characteristics in mature individuals of several herbaceous species growing in the understory of a tropical moist forest in central Panama. Our objective was to see if contrasts in leaf physiology among Crassulacean acid metabolism (CAM)and C3 plants were associated with differences in whole-plant structure or performance in a habitat that is considered atypical for CAM. Foliage of Aechmea magdalenae, an understory CAM bromeliad, has a higher maximum photosynthesis rate, and greater nitrogen, chlorophyll, and water contents on a leaf-area basis compared to three sympatric C3 species. Leaf characteristics of two other understory CAM bromeliads, Ananas comosus and Bromelia plumieri, were similar to that of Aechmea. Aechmea, compared to three sympatric C3 species, allocates less biomass to roots and more to foliage. The annual aboveground relative growth of Aechmea was lower than it was for the C3 species, despite Aechmea's higher photosynthetic capacity. This is consistent with the hypothesis that the efficient use of transient periods of high light for carbon gain is critical to the success of this CAM species as an understory plant. Maximum growth in Aechmea occurred during the dry season, whereas for the C3 species growth was greatest during the wet season, suggesting that variation in photosynthetic pathway can provide a basis for temporal niche differentiation among tropical forest herbaceous perennials.
Keywords: AECHMEA MAGDALENAE; BARRO COLORADO ISLAND; BIOMASS ALLOCATION; BROMELIAD; C3; CRASSULACEAN ACID METABOLISM; NICHE; PANAMA; PHOTOSYNTHESIS; PLANT GROWTH; SUNFLECKS; TROPICAL FOREST